PERAN MEDIA COVERAGE ATAS PENGARUH CORPORATE GOVERNANCE DAN PENGUNGKAPAN MANAJEMEN RESIKO TERHADAP REAL EARNINGS MANAGEMENT - Herawati, Vinola; Daeli, Florus; Julia (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
This study aims to examine the effect of corporate governance and risk management disclosure on real earnings management. In addition, this study also investigates the role played by the media (media coverage) and examines whether the media has an influence on real earnings management. The data analysis method in this study is a causality test using multiple regression analysis with moderation (Moderated Regression Analysis). The sample for this study used purposive sampling with a sample of consumer goods sector companies on the Indonesia Stock Exchange for the period 2019 – 2021. The results showed that independent commissioners and audit committees have a negative effect on real earnings management, disclosure of risk management and media coverage have no effect on real earnings management. Media coverage strengthens the influence of the Independent Commissioner on real earnings management, but does not strengthen the influence of the Audit Committee on real earnings management.